Serum TNF-α and Its Association with Glycaemic Control in Type 2 Diabetes Mellitus: A Comparative Cross-Sectional Study - Mukul Vyas; Bhavana Tiwari; Rohit Manyal; Rajeev Lohokare (International Journal of Science and Healthcare Research, 2026)
Background: Chronic low-grade inflammation is increasingly recognized as an important component of the pathophysiology of type 2 diabetes mellitus (T2DM). Tumor necrosis factor-alpha (TNF-α), a pro-inflammatory cytokine implicated in insulin resistance, may be associated with worsening glycaemic control. This study compared serum TNF-α concentrations between individuals with T2DM and healthy controls and evaluated the association between TNF-α and glycated haemoglobin (HbA1c). Methods: This comparative case-control study included 120 participants, comprising 60 individuals with T2DM and 60 age- and sex-matched healthy controls. Clinical and biochemical parameters were recorded. HbA1c was measured by ion-exchange high-performance liquid chromatography, while serum TNF-α concentrations were determined using an enzyme-linked immunosorbent assay. TNF-α concentrations were compared between study groups and across HbA1c categories among participants with T2DM. Pearson correlation analysis was used to assess the relationship between TNF-α and HbA1c. Binary logistic regression was performed to identify variables associated with T2DM status. Receiver operating characteristic (ROC) analysis was used to evaluate the discriminatory performance of TNF-α, HbA1c, and their combined model. Results: Serum TNF-α concentrations were significantly higher in participants with T2DM than in controls (34.8 ± 9.6 vs. 13.7 ± 4.3 pg/mL; p9.5% (p